Absorption coefficient estimation of thin MoS2 film using attenuation of silicon substrate Raman signal - Kwak, Joon Young (Elsevier BV, 2019)
A simple, non-destructive, and convenient method using Raman spectroscopy and Atomic Force Microscopy for extracting the absorption coefficient of MoS2 is presented. The attenuation of the substrate Raman signal intensity due to the MoS2 overlayer is found to be dependent on the MoS2 film thickness estimated from the AFM measurements. Using the light attenuation model from the measurements, the experimentally extracted absorption coefficient of the thin MoS2 flakes is determined to be 2.8x10(6) cm(-1). This simple technique is capable of estimating the absorption coefficient of other two-dimensional layered materials.